Peruvian Educational Profile 2010 - De La Cruz, Alexander (2011)
This research seeks to identify preferences expressed by students studying at a particular university, by the same way is to measure the students’ interest in ex- ploring new professional and technical careers, feasible to be offered by the Uni- versidad Peruana Unión. In relation to the objectives, a questionnaire was applied directly to all the students who are graduating from fourth and fifth grade, making a whole of 555 young people. The results could be found that 61.4% of young people prefer private universities. From the whole sample of 555, the 27.5% are Adventist students and they would like to study at the Universidad Peruana Union. The results of these tests were analyzed through statistical analysis package in Visual Basic educational research, through analysis of absolute frequencies and percentages, mean and mode. Young people from schools Adventists Department of San Martin have a preference for private universities.